Pengembangan Sistem Informasi Purchasing Order Berbasis Web pada PT. Karya Teknik Mandiri - Muhammad Agusalim Hariadi; Retno Indah Rokhmawati; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
According to the interviews with the director of PT. Karya Teknik Mandiri, it is concluded that PT. Karya Teknik Mandiri has problems in the business process of purchasing order. These problems are, frequent mismatches between mailing letters with customer purchasing orders, broken or lost purchasing order customers, and the difficult of customer communication with the company in discussing the purchase. Therefore, given a solution by replacing the current business process conditions into the proposed business process with the application of information systems equipped with service automation features for business process purchasing order PT. Karya Teknik Mandiri. System development method using Prototype method and Operational CRM approach of Service Automation module. System test is done with Validation Testing and User Acceptance Testing, with test result has 100% valid value and acceptance value